2019
DOI: 10.4049/jimmunol.1900001
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Peptidome of the Bat MHC Class I Molecule Reveal a Novel Mechanism Leading to High-Affinity Peptide Binding

Abstract: Bats are natural reservoir hosts, harboring more than 100 viruses, some of which are lethal to humans. The asymptomatic coexistence with viruses is thought to be connected to the unique immune system of bats. MHC class I (MHC I) presentation is closely related to cytotoxic lymphocyte immunity, which plays an important role in viral resistance. To investigate the characteristics of MHC I presentation in bats, the crystal structures of peptide–MHC I complexes of Pteropus alecto, Ptal-N*01:01/HEV-1 (DFANTFLP) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 64 publications
0
61
0
1
Order By: Relevance
“…This study showed that bat MHC molecules can accommodate larger peptides, compared to other mammals and have unique consensus-binding motifs, potentially as a result of their co-evolution with viruses (125). The MHC class I protein complexes (126) in P. alecto were recently crystallized, revealing three additional amino acids in bat MHC class I (methionine, aspartic acid and leucine), compared to other selected mammals (127). The three amino acids formed an additional salt bridge that could potentially present high affinity peptides during the peptide exchange process in bat cells facilitating an efficient cell-mediated immune response.…”
Section: Immune Cell Populations In Batsmentioning
confidence: 84%
“…This study showed that bat MHC molecules can accommodate larger peptides, compared to other mammals and have unique consensus-binding motifs, potentially as a result of their co-evolution with viruses (125). The MHC class I protein complexes (126) in P. alecto were recently crystallized, revealing three additional amino acids in bat MHC class I (methionine, aspartic acid and leucine), compared to other selected mammals (127). The three amino acids formed an additional salt bridge that could potentially present high affinity peptides during the peptide exchange process in bat cells facilitating an efficient cell-mediated immune response.…”
Section: Immune Cell Populations In Batsmentioning
confidence: 84%
“…We identified 174 potential SARS-CoV-2 vaccine candidate peptides, out of which 48 have been previously deposited in IEDB following various studies (Qu et al 2019;Blicher et al 2005;Sylvester-Hvid et al 2004;Harndahl et al 2006;Sidney et al 2006;Ishizuka et al 2009) . The majority of the previously deposited peptides were measured in one or multiple affinity assays and reached low Kd (<50 nM) values, indicating strong affinity.…”
Section: Discussionmentioning
confidence: 99%
“…The nonapeptides used in the study (see Supplemental Table I) and one synthetic random peptide library, Ran_9X splitted (9X, XXXXXXXXX, where X is a random amino acid other than cysteine), were synthesized and purified by reverse-phase HPLC and mass spectrometry (MS) (SciLight Biotechnology) with .95% purity. The lyophilized peptides were stored at 280˚C and dissolved in DMSO at a concentration of 25 mg/ml before use as previously described (31).…”
Section: Peptide Synthesismentioning
confidence: 99%